(untitled) (III International Congress of Biotechnology and Neotropical Ecosystems, 2026)
Local Amazonian populations are exposed to mercury (Hg) contamination risks due to high fish consumption, a phenomenon influenced by processes of bioavailability, bioaccumulation, and biomagnification derived from natural sources or human activities. This study aimed to determine total Hg concentrations in key fish species marketed and consumed by communities in the Ecuadorian Amazon in order to propose consumption recommendations. A total of 151 fish specimens were collected from markets, collection centers, and through artisanal and sport fishers during May and June 2018, representing the minimum locally available catch. Each specimen was taxonomically identified, measured, weighed, and recorded according to collection site, and between 2 and 10 g of muscle tissue were extracted. Samples were freeze-dried and analyzed at the GET Laboratory in Toulouse, France, using direct atomic absorption spectrophotometry (Milestone® DMA-80). Twenty species belonging to eight families and three orders were identified and classified into eight trophic roles, showing diverse Hg concentration patterns according to ecological position and body size. Ninety-seven percent of catfish species (Pimelodidae), classified as carnivores and scavengers, exceeded by up to five times the maximum Hg limits recommended by the WHO and EPA-FDA for human consumption (p ≤ 0.05). Species with the lowest Hg concentrations, and therefore more suitable for consumption, were found in the upper sections of river basins, whereas greater bioaccumulation was observed in lower sections, with an inverse relationship between altitude and capture size. The study concludes that Hg contamination is present in fishery resources of the Ecuadorian Amazon, particularly in catfish species, which are under greater fishing pressure from local markets. Subsistence fishing, however, presents variable risks depending on the extraction site.